Effects of oral of administration of monoglycide laurate on virus load and inflammation in PEDV infected porcine - Liu, Zheyan; Zhu, Ling; Zhao, Xiaonan; Liu, Jian; Cheng, Huangzuo; Zhang, Lina; Tang, Huaqiao; Sun, Xiangang; Hu, Youjun; Xu, Zhiwen (Frontiers in Veterinary Science, 2022)
To investigate the effect of monoglyceryl laurate (GML) against PEDV in vivo, this study was conducted to investigate the clinical signs, pathological changes, tissue viral load and cytokine levels of piglets in each test group (low-dose treatment group A1 , medium-dose treatment group A2 , high-dose treatment group A3 , blank control group B and virus control group C) and to evaluate the protective effect of different doses of GML by establishing an animal infection model. The results showed that compared with group C, group A could reduce the mortality rate of piglets, among which the protection rates of groups A2 and A3 were comparable and could reach 100%; the trend of weight loss of piglets was effectively slowed down and growth performance recovered; the pathological damage of intestinal tract was significantly reduced; the viral load in intestine and mesenteric lymph nodes were reduced; the levels of IL-8 and TNF-α in the blood of group A were reduced, among which the anti-inflammatory effect of group A3 was better than that of groups A1 and A 2The anti-inflammatory effect was better in group A than in group A and group A in a dose-dependent manner. Our study suggests that GML has good anti-PEDV effects in vivo.